condición educativa de los niños, niñas, y adolescentes en situación migratoria y de movilidad humana en el cantón Catamayo - Agreda Díaz, Christopher Misael (2024)
The present Curricular Integration Work is entitled Educational Condition of the children, and teenagers in migratory condition at Catamayo, which is realized whit the general objective of Analyze, Understanding clearly way, using specific figures given by professionals in the topic, trying to explain what is the actual educational condition of the migrants children , which are their responsibilities, their limitations, and essentially, how are they living , trying to generate change proposals that makes differences this bad reality where they are, even when our Constitution recognize the universal citizen condition, and is a warranted rights book, many of this rights are violated because of the discrimination, xenophobia, and racism, the social ways to work the publics politics ends up without being inclusive, the poor and the discrimination are the reasons that disable the migrant rights.